Linear dimensional changes of denture base and hard chair-side reline resins after disinfection - Gonçalves, Andréa [UNESP]; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2006)
Objectives: This study evaluated the effect of disinfection by immersion in sodium perborate (50 degrees C/10 min) or microwave irradiation (650 W/6 min) on the linear dimensional change (LDC) of four reline resins (Kooliner-K, New Truliner-N, Tokuso Rebase Fast-T, Ufi Gel Hard-U) and one heat-polymerizing denture base resin (Lucitone 550-L). Methods: Specimens (50.0 mm diameter, 0.5 mm thickness) were made using a split mold with reference points, and divided into two controls and four test groups (u = 8). The distances between the points were measured on the mold (baseline readings), and compared to those obtained from the specimens after: polymerization or immersion in water (37 degrees C) for 7 days (controls); 2 or 7 cycles of disinfection by immersion or microwave irradiation. Results: the two-way ANOVA and Tukey's test (alpha = 0.05) showed that microwave disinfection significantly increased the mean LDC of materials L (-1.43%), N (-1.27%) and K (-1.06%). Material N also exhibited a significant increase in LDC after two cycles of chemical disinfection (-0.73%). For U (-0.47%) and T (-0.21%) materials, no significant changes in LDC were found. Conclusions: Microwave disinfection increases the shrinkage of materials L, N, and K. The dimensional stability of resins U and T was not affected by the disinfection methods evaluated. (c) 2006 Wiley Periodicals, Inc.
Keywords: dental polymers; irradiation; linear